Zootaxa 20th Anniversary Celebration: section Acanthocephala - Monks, Scott (Zootaxa, 2021)
Of 32 papers including Acanthocephala that were published in Zootaxa from 2001 to 2020, 5, by 11 authors from 5 countries, described 5 new species and redescribed 1 known species and 27 checklists from 11 countries and/geographical regions by 72 authors. A bibliographic analysis of these papers, the number of species reported in the checklists, and a list of new species are presented in this paper.